Pengembangan Video Pembelajaran Tutorial Sujud pada Mata Pelajaran Pendidikan Agama Islam pada Sekolah Menengah Pertama: Development of Video Learning Tutorials of Prostration in Islamic Religious Education Subjects in Junior High Schools - Fahyuni, Eni Fariyatul; Aini, Wilna (Universitas Muhammadiyah Sidoarjo, 2019)
Learning is a process and the students towards a better direction. Islamic Education as one of the subjects taught in schools not only function as a transfer of knowledge but also teaches values and norms to practice them in their daily lives. The application of Islamic religious education in Indonesia is not maximum, there are still many shortcomings and weaknesses both in terms of the quality of teaching and the quality produced by the students. The development of sujud tutorial learning videos is the development of learning media that aims to improve students' understanding and learning outcomes in prayer and prostration material. This type of research and development is known as Research and Development which is carried out to produce products and prove the effectiveness of the products produced. The results of the material validation expert about prayer and prostration were 90%, while the validation of media experts also produced a value of 92%, which means